Working Time Changes: Social Integration through Transitional Labour Markets - Tremblay, Diane-Gabrielle (Relations Industrielles / Industrial Relations, 2003)
Reviews the book 'Working Time Changes: Social Integration Through Transitional Labour Markets,' by Jacqueline O'Reilly.
Keywords: BOOKS -- Reviews; Nonfiction; O'REILLY, Jacqueline; WORKING-Time Changes: Social Integration Through Transitional Labor Markets (Book); Working hours